Electrophysiological characteristics of right- and left-sided Mahaim accessory pathways: A single-center experience in China - Chen, Mingxian; Wang, Zhuo; Wang, Songyun; Liu, Zhenjiang; Li, Xuping; Yang, Hui; Hu, Lin; Wu, Zhihong; Li, Qiming; Zhou, Shenghua (Frontiers in Cardiovascular Medicine, 2022)
Background Mahaim-type accessory pathways (MAPs) are rare accessory pathways (APs) with specific properties. They are mostly located in the right side of the heart but rarely exist on the left side. Objectives This study aims to analyze the clinical and electrophysiological (EP) characteristics of both-sided MAPs. Methods A total of 2,249 patients with AP from our center were enrolled between 1 January 2011 and 27 March 2022. During the EP study (EPS) 17 patients were diagnosed with MAPs (right-sided: n = 13, left-sided: n = 4) according to the properties of Mahaim fibers. Results MAPs constitute 0.75% of all APs. Out of 1,553 patients with left-sided APs, four patients (0.26%) were diagnosed with Mahaim fiber-mediated tachycardia. Out of 696 patients with right-sided APs, 13 patients (1.9%) were diagnosed with Mahaim fiber. Most Mahaim fibers were located at the free wall of the tricuspid and mitral annuli. Seven patients of right-sided MAPs were of atriofasicular type, six patients had right-sided MAPs, and all of the patients with left-sided MAPs were of atrioventricular (AV) type. The M potential only was detected in long-length MAPs. Coexistence with other supraventricular tachycardias (SVTs) was also observed both in patients with right-sided and left-sided MAPs. All the patients underwent radiofrequency ablation successfully. Only one patient had tachycardia recurrence during a follow-up. Conclusion Although MAPs are commonly located at right sides, left sites are not impossible. The M potential contributes to the improvement of the successful ablation.